Digital Safety of Journalists in Lagos State - Idris Mohammed; Omolara Oluwabusayo Akin-Odukoya; Omotola Ogunbola; Adebayo Aisha Omoronike; Muhammad Ridwan (Budapest International Research and Critics University, 2024)
Digital safety for journalists in Lagos state is a complex and pressing issue that requires urgent attention. With the advancements in technology, journalists in Lagos state have embraced digital tools to disseminate information to their audience. However, this has also exposed them to various forms of digital threats such as cyber attacks, online harassment, and surveillance. The objectives of the study are to examine the magnitude of online attacks on journalists in Lagos State; to explore the online threats to journalists in Lagos State and to find out the consequences of the online attacks on journalists in Lagos State. The study employed the Protection Motivation Theory (PMT). The positivist approach of research design was adopted which informed the choice of survey method to generate data. Stratified sampling technique was adopted, which is a sampling method that deals with dividing the population of a study into groups called strata or stratum. Thus, this study stratified the population into, television, radio and newspaper from journalists in the media organizations were selected for study. The instrument of data collection for this study is questionnaire and frequency and percentage was used to present the data. The study concludes that Nigeria lacks adequate development which is not farfetched as it is seen in our society, the carious impediment of this development both politically and in all sphere are caused by corruption manifested in different form at different levels as identified in the course of the study: bribery, nepotism, embezzlement and misappropriation of funds. This has led to lack of political participation, lack of public trust in the government and weaken democratic institutions.